1990
DOI: 10.1002/apmc.1990.051810102
|View full text |Cite
|
Sign up to set email alerts
|

Thermal degradation of poly(vinyl chloride) blends

Abstract: Poly(viny1 chloride) was mixed with various poly(methacry1ate)s and polycarbonates by combined precipitation from common solutions. The thermal stability of the samples was measured at 180 "C under nitrogen, the HCI evolved was detected by conductometry.UV-Vis-spectra of degraded samples were measured to investigate the influence of the poly(methacry1ate)s on the lengths of polyenes formed during the degradation of poly(viny1 chloride).The experiments show that the nature of the ester group is the dominating f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…314 These are essential parameters which affect duration of heat exposure but there are many other data characterizing thermal stability of PVC/PMMA blends. 308 The thermal decomposition temperatures of the first and second stage of degradation in PVC in the blend with PMMA were higher than for pure PVC. Lowering weight loss in the first stage of blend degradation (dehydrochlorination) should be attributed to dilution of HCl producing polymer (PVC) by PMMA.…”
Section: Poly(methyl Methacrylate) Pmmamentioning
confidence: 88%
See 3 more Smart Citations
“…314 These are essential parameters which affect duration of heat exposure but there are many other data characterizing thermal stability of PVC/PMMA blends. 308 The thermal decomposition temperatures of the first and second stage of degradation in PVC in the blend with PMMA were higher than for pure PVC. Lowering weight loss in the first stage of blend degradation (dehydrochlorination) should be attributed to dilution of HCl producing polymer (PVC) by PMMA.…”
Section: Poly(methyl Methacrylate) Pmmamentioning
confidence: 88%
“…Poly(methyl methacrylate) and other methacrylates are used as process aids, 308 and they improve PVC stiffness and heat distortion. 309 There is no single answer regarding blend miscibility because it depends on conditions of its preparation.…”
Section: Poly(methyl Methacrylate) Pmmamentioning
confidence: 99%
See 2 more Smart Citations
“…The concentration dependency of evaporation of plasticizer led to some con-troversy, where Braun and et al have shown the relationship not to be linear and having a minimal value based on the chosen plasticizer and possible interactions. 65,66 The highest compatibility of a plasticizer with polymer is designated as the critical concentration, but no studies were found to connect it with the lowest evaporation rate.…”
Section: Degradation Processes Involving Plasticizersmentioning
confidence: 99%